Small heat shock proteins: big folding machines - Morrow, Geneviève (Cell Stress Chaperones, 2014)
The workshop was entitled “The Small HSP World” and had the mission to bring together investigators studying small heat shock proteins (sHSPs). It was held at Le Bonne Entente in Quebec City (Quebec, Canada) from October 2 to October 5 2014. Forty-four scientists from 14 different countries attended this workshop of the Cell Stress Society International (CSSI). The small number of participants stimulated interesting discussions, and the resulting informal atmosphere was appreciated by everybody. This article provides highlights from talks and discussions of the workshop, giving an overview of the latest work on sHSPs.